Prevalência das técnicas de reconstrução nasal utilizadas nos últimos quatro anos em serviço de Cirurgia Plástica do Ceará - William de Almeida Machado; Salustiano Gomes de Pinho Pessoa (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Nasal skin lesions are significance in plastic surgery because of the difficult of aesthetic and functional reconstruction. Central position of the nose on the face, and its structure, rigid architecture, and low mobility are among the possible causes. Several techniques used to correct nasal defects have been documented since the origins of plastic surgery. We evaluated retrospectively and analyzed the main surgical techniques and their indications in cases of nasal reconstruction performed at the Plastic Surgery Service of Ceará over a period of 4 years. METHODS: This was a retrospective clinical study including 151 patients who underwent resection of nasal lesions from January 2010 to December 2014 at a public hospital in Fortaleza. Variables included were sex, age, and surgical technique. RESULTS: Most of patients were men with a mean age of 63.2 years, they accounted for 52.3% of the sample. The main reconstruction forms were primary suture (28.5%), rotational flap (22.5%), bilobate (14.6%), advancement flap (8.6%), nasogenian (6%), frontal (4.7%) and skin graft (15.2%). CONCLUSION: Because of the different nasal reconstruction possibilities, the surgical technique choice, after resections, should consider defect location and size, contour and nasal anatomy for a better aesthetic and functional result. At our service, reconstruction with primary lesion synthesis was predominant with a slight predominance among men and older patients. Other techniques were used given the preference for better aesthetic and functional result for each patient.